Genetic Diversity of Field Pea Genotypes (Pisum sativum L.) in Relation to their Plant Type using Multivariate and Genotype-by-Trait Biplot Analysis - Assen, Kedir Yimam; Haile, Gebeyaw Achenef; Shuro, Aliyi Robsa (International Journal of Economic Plants, 2024)
The present study was conducted during June–November, 2019 at Bekoji and Kofele substation of Kulumsa Agricultural Research Center (KARC) with the aim to assess the genetic diversity among field pea genotypes for desired morpho-agronomic traits. A total of 49 Field pea genotypes, representing two different plant types were evaluated for 13 characters. Through cluster analysis, the genotypes were grouped into five categories based on the Euclidean distance matrix using the complete linkage method. Cluster one had the most genotypes (20), while cluster five had the fewest (2). Genetic distances among genotypes estimated by Euclidean distances from 13 traits ranged from 14.76 to 5514.77. Principal component and biplot analyses showed that seed yield, plant height, days to 90% maturity, number of pods per plant and seeds per plant were the main factors contributing to genotype divergence. Additionally, genotypes in the prostrate (leafed) type of field pea had a greater genetic distance (diversity) compared to those in the erect (semi-leafless) type. In general this study showed the presence of considerable diversity for the studied traits in field pea genotypes, with differences between plants types even though the dendrogram and PCA didn’t show clear cut (distinct) grouping pattern in field pea genotypes with respect to their plant types and sources. This implies an opportunity for improving desired traits in a field pea breeding program through selection or hybridization of these divergent genotypes. Thus, crossbreeding promising parents, especially selected from advanced prostrate and erect types, can result in a good level of genetic recombination.